Profile of Patients Who Died During One Year in the Pneumophthisiology Department of the Hospital National Ignace Deen CHU in Conakry - Boubacar Djelo Diallo; Ibrahima Sory Dialli; Thierno Hassane Diallo; Oumou Hawa Diallo; Alpha Oumar Barry; Camara Lansana Mady (Journal of Respiratory Diseases, 2024)
Introduction Mortality is one of the most important demographic phenomena in public health, and its rate is the primary indicator of a population's state of health. The aim of this study was to describe the profile of patients in the pneumo-phthisiology department of the Hospital National Ignace Deen CHU in Conakry. Methodology This was a retrospective descriptive study lasting one year, from 01 January to 31 December 2023, on 176 records of hospitalized patients who died in the pneumophthisiology department of the Ignace Deen National Hospital. Results A total of 1043 patients were hospitalized during our study period, 176 of whom died, giving a mortality rate of 16.87%. The mean age of the deceased patients was 49.57±18.8 years, with a male predominance (sex ratio=1.93). Clinical signs on admission were dominated by dyspnoea (70.45%) and chest pain (61.36%). Tuberculosis was the most common diagnosis with a frequency of 42.61%, followed by TB/HIV co-infection with a frequency of 22.16%. The average length of hospitalization was 8.79 days. Probable cause of death was dominated by respiratory distress (54.44%) and decompensated anaemia (32.95%). Conclusion Mortality in the pneumo-phthisiology department of the Ignace Deen National Hospital remains high. Anemia and respiratory distress were the most common diagnoses of severity, hence the need to improve management of these probable causes of death.
Keywords: Profile